Abrogation of simian virus 40 DNA-mediated transformation of primary C57BL/6 mouse embryo fibroblasts by exposure to a simian virus 40-specific cytotoxic T-lymphocyte clone. - Karjalainen, H E (1985)
Primary mouse embryo fibroblasts of C57BL/6 origin (B6/MEF) were transformed in vitro by transfection with simian virus 40 (SV40) DNA. The transformation frequency was markedly reduced if the SV40 DNA-transfected cultures were briefly exposed to K11 cells, an SV40-specific clone of cytotoxic T lymphocytes. This abrogation of SV40 transformation in vitro by cytotoxic T-lymphocyte clone K11 was specific, since transformation of B6/MEF cells by adenovirus type 5 DNA was not affected. The approach described here should serve as an ideal model of dissecting immunological events during in vivo tumorigenesis.